Carbon Dots Dispersed on Graphene/SiO2/Si: A Morphological Study. Issue 3 (7th January 2019) - Faggio, Giuliana; Gnisci, Andrea; Messina, Giacomo; Lisi, Nicola; Capasso, Andrea; Lee, Gwan Hyoung; Armano, Angelo; Sciortino, Alice; Messina, Fabrizio; Cannas, Marco; Gelardi, Franco Mario; Schilirò, Emanuela; et al.
Abstract : Low‐dimensional carbon materials occupy a relevant role in the field of nanotechnology. Herein, the authors report a study conducted by atomic force microscopy and Raman spectroscopy on the deposition of carbon dots onto graphene surfaces. The study aims at understanding if and how the morphology and the microstructure of chemical vapor deposited graphene on Si/SiO2 may change due to the interaction with the carbon dots. Potential alteration in the graphene's electrical properties might be detrimental for optoelectronic applications. The deposition of carbon dots dispersed in water and ethanol solvents are explored to investigate the effect of solvents with different fluidic properties. The obtained results indicate that the carbon dots do not alter the quality of graphene. Abstract : Atomic force microscopy and Raman spectroscopy are used to study the morphological and structural properties of the carbon dots/graphene nanocomposites supported on SiO2 /Si substrate in order to understand if and how the properties of the native materials are modified because of their interaction. The obtained results indicate that the carbon dots do not alter the quality of graphene.